Board games: gerotechnology in nursing care practice - Paula Cristina de Andrade Pires Olympio; Neide Aparecida Titonelli Alvim
ABSTRACT Objective: To create a board game as a form of gerotechnology to promote active and healthy aging. Method: This was a qualitative, convergent care study conducted with 32 older adults. Individual interviews, creativity and sensitivity techniques, group discussions, and participant observations guided by Paulo Freire's theoretical framework of problematization were used to produce data. The participants and researchers assessed the entire production process at the end of the study, after the gerotechnology was implemented in the groups. French discourse analysis was adopted. Results: Patented under registration no. BR 1020160107725, the game was created as a technological product based on the discussions with older adults, considering the conceptions, knowledge and practices shared by them about aging. Final considerations: The gerotechnology implemented in clinical nursing practices functioned as a playful resource to exercise self-determination and independence among older adults, boosting memory, self-esteem, socialization processes, exchanging experiences and shared learning.